Programas Sociais Corporativos e Capital Social: Proposta de Qualificação - Janaina Macke; Rosinha Machado Carrion; Eliete Kunrath Dilly (RAC: Revista de Administração Contemporânea, 2010)
There is a discourse that has already spread in the social imaginary that identifies the company as the best qualified actor for solving social problems, given their competence when it comes to facing the globalized and competitive market. Nevertheless, we argue that behind this point of view there is a reductionist view concerning the complexity of social facts, considering social problems simply as efficient and effective management resources. This study is based on empirical research that was conducted in seven enterprises in Rio Grande do Sul State. The companies won the Social Responsibility Award from the Legislative Assembly of Rio Grande do Sul. We used a multiple case study and a content analysis technique. The results show a weak relationship link between companies and the people who benefited, a low level of structured programs and an overlap of programs working with the same target public. The article points out the limits of the social programs and proposes a model – based on the social capital theory - in order to qualify them so that they can strengthen their contribution to building a more balanced society.